Performance Effectiveness of Employees of the Regional Development Planning Agency of North Sumatra Province during the Covid-19 Pandemic - Umi Nabila Suci; Marliyah Marliyah (Penerbit Jurnal Indonesia, 2022)
This journal aims to determine the effectiveness of employee performance during the Covid-19 pandemic at the Regional Development Planning Agency Office of North Sumatra Province. The method used in this research is qualitative and data collection techniques through the apprenticeship process, observation and interviews. The results of this study indicate that the level of effectiveness of the performance of the Provincial Planning Development Agency office employees is in the effective category, this proves that Bappeda Provsu employees have been able to carry out responsibilities, foster good cooperation and can provide good administrative services.